Current status and barriers in pulmonary hypertension care delivery in India: A qualitative analysis. (21st June 2022) - Maligireddy, Anand Reddy; Shore, Supriya; Sreenivas Kumar, A.; Harikrishnan, S.; Ajit Mullasari, S.; Sastry, B. K.; Gupta, Sameer; Choudhary, Nikhil; Atreya, Auras R.; Arora, Sonali; Moles, Victor M.; Mclaughlin, Vallerie V.; et al.
Abstract: Although pulmonary hypertension (PH) is widely prevalent in India, care delivery for this condition has unique challenges in a lower middle‐income country (LMIC). To describe care delivery for patients with PH and associated barriers in India. We interviewed physicians across eight healthcare systems in India about PH clinical care using semi‐structured enquiries to understand care delivery and associated challenges in their specific practice as well as the associated health system. Qualitative analysis was performed using content analysis methodology. Physicians reported that common causes for PH in their practice were rheumatic mitral valve disease, coronary artery disease, and congenital heart disease (CHD). No center had a dedicated PH program. Only one center had a specific protocol for PH management. Diagnostic evaluations were limited, and right heart catheterizations were recommended for patients with CHD. Pulmonary vasodilator therapy was used for severe symptoms or markers of severe disease. Agents used to treat PH were widely variable across physicians and prostacyclins are unavailable in India. Barriers included limited training in PH for physicians, lack of consensus guidelines for PH specific to LMIC, and lack of financial incentives for health care systems to organize dedicated PH programs. Other barriers included poor patient health literacy and socioeconomic barriers that limit ability to test and treat PH. PH care delivery in India is variable with widely differing clinical practices. Dedicated training in PH management and establishing guidelines specific to LMIC like India can form the first step forward.